New oxide ion conducting solid electrolytes, Bi4V2O11: M; M = B, Al, Cr, Y, La - Lee, Chnoong Kheng; Bay, Boon Hong; West, Anthony R. (Royal Society of Chemistry, 1996)
The compositional ranges of Bi4V2O11 solid solutions containing trivalent cations: B, Al, Cr, Y and La have been determined by means of a phase diagram study at solidus temperatures, ca. 850°C. At least three mechanisms for accommodating variable cation contents are required. These are nominally V → Bi, V → M, Bi → M; the first two also involve the formation of anion vacancies. The detailed mechanisms by which ions as different in size as B and La can enter the Bi4V2O11 structure cannot, however, be inferred from the phase diagrams. Phase diagrams at 500°C have much smaller solid-solution areas, indicating the stability and extent of the solid solutions to be very temperature-dependent. Conductivity studies show that La-, Y- and Al-doped materials, with a composition around Bi4V1.8M0.2O10.8, are the best conductors at 300°C with a conductivity value of up to 1.4 × 10–4Ω–1 cm–1. At 600°C, Al-doped materials have the highest conductivity, ca. 1 × 10–1Ω–1 cm–1. Conductivity Arrhenius plots show changes of slope associated with the phase transitions: α→β→γ for B, Al, Cr and β→γ for Y: data for La (γ-polymorph only) are almost linear.